Driving Factors of Cloud Accounting Implementation in Small and Medium Enterprises (SMEs): Evidence from Indonesia - Hamzah Ritchi; Yahya, Bernardo; Roshi Dwiokta; Sugianto, Larasati P.M. (Indonesian Journal of Information Systems, 2024)
This paper attempts to identify key factors that affect Small and Medium Enterprises (SMEs) decision in implementing cloud accounting system on their business, in particular Indonesia’s Bandung region. Bandung greater area has long been recognized as among the amiable region for SME development in the economy. This research qualitatively analyzed primary data obtained through a series of in-depth interviews with SMEs key personnel regarding the opportunity of cloud-based accounting. The informants were eight key SMEs personnel selected for their relevant knowledge and experience in accounting and associated technology use. An expert-based validation was then conducted on factors that were successfully identified at coding stage. The findings indicate that there are seven decisive factors which influence SMEs decision including security, usability, human resource, time, communication, cost, and functionality. This research offers an insight regarding the implementation of cloud accounting in SMEs by filling the identified gap to the body of literature in cloud accounting and SMEs in particular developing economy.